2022
DOI: 10.7759/cureus.27688
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Yoga on Bipolar Disorder: A Systematic Review

Abstract: Bipolar disorder (BD) is a mood disorder characterized by severe mood swings and or periods of depression. This study examined the role that practicing yoga has on the symptoms of BD. One of the main goals was to identify if patients with BD believe that yoga is a viable treatment option. Six research databases were searched using the keywords "yoga" AND "therapy" AND "BD" AND "bipolar depression." Articles published in 2005 and later were included in the search. After duplicates were removed, and inclusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition to being a traditional spiritual practice that incorporates breathing techniques, body movements, meditation, philosophical discussions, and lifestyle choices, yoga is an age-old health therapy (Cramer et al, 2016(Cramer et al, , 2019Tellhed et al, 2019). Through the integration of mind and body, yoga can be utilized as a supplemental therapy that effectively reduces pain, tension, anxiety, and depression (Gothe et al, 2019;Jean et al, 2022;Sarla, 2020). Additionally, yoga enhances the lubrication and joint function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a traditional spiritual practice that incorporates breathing techniques, body movements, meditation, philosophical discussions, and lifestyle choices, yoga is an age-old health therapy (Cramer et al, 2016(Cramer et al, , 2019Tellhed et al, 2019). Through the integration of mind and body, yoga can be utilized as a supplemental therapy that effectively reduces pain, tension, anxiety, and depression (Gothe et al, 2019;Jean et al, 2022;Sarla, 2020). Additionally, yoga enhances the lubrication and joint function.…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity and mental relaxation techniques are one of the most important non-pharmacological ways of controlling cardiovascular and mental health. Studies have reported that yoga can improve depression in patients suffering from bipolar disorder [ 16 ]. It also helps in reducing attention-deficit hyperactivity disorder [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoga is an ancient health therapy as well as a traditional spiritual practice including body movements, breathing exercises, meditation, philosophical lectures, and lifestyle (Cramer et al, 2016(Cramer et al, , 2019Tellhed et al, 2019). Yoga can be used as a complementary medicine, through the union of mind and body, which is effective in reducing stress, anxiety, depression, and pain (Gothe et al, 2019;Jean et al, 2022;Sarla, 2020).…”
Section: Introductionmentioning
confidence: 99%